Decision-making for solar panel selection using Sugeno-Weber triangular norm-based on q-rung orthopair fuzzy information - Wang, Yibo; Hussain, Abrar; Yin, Shi; Ullah, Kifayat; Božanić, Darko (Frontiers in Energy Research, 2024)
Solar power is an alternative energy derived from natural resources like sunlight. Solar power makes a friendly environment and is less harmful than burning fossil fuels, which causes harmful greenhouse gas emissions. To evaluate a reliable solar panel based on certain characteristics by incorporating the theory of the decision-making process. To serve this goal, discuss a well-known aggregation model of the q-rung orthopair fuzzy set, which is a broader and flexible environment of fuzzy sets and intuitionistic fuzzy sets used to handle unpredictable information of human opinion. The key components of this article are to demonstrate some realistic operations of Sugeno-Weber triangular norms in light of q-rung orthopair fuzzy information. These operations provide authentic estimated information during the decision-making process. We developed a class of new aggregation operators under the q-rung orthopair fuzzy information system, including q-rung orthopair fuzzy Sugeno-Weber power weighted average and q-rung orthopair fuzzy Sugeno-Weber power weighted geometric operators. Some realistic characteristics and special cases are also demonstrated to show the compatibility of proposed methodologies. An innovative approach of the multi-attribute decisionmaking problem is utilized to resolve different real-life applications under considering various criteria or attributes. To show the intensity and applicability of the proposed approaches, we explored a numerical example to select an efficient solar panel based on the proposed methodologies. The authors also presented a comprehensive comparison technique to compare the findings of existing methods with proposed aggregation approaches. Finally, the proposed research work is summarized in a single paragraph.